Gene Editing and Genome Engineering with CRISPR-Cas9 - Emmanuelle Charpentier (Molecular Frontiers Journal, 2017)
The RNA-programmable CRISPR-Cas9 technology allows precise and efficient engineering or correction of mutations, modulation of gene expression and marking of DNA in a wide variety of cell types and organisms in the three domains of life. Because of its versatility and ease of design, this powerful technology has been rapidly and universally adopted for genome editing applications in life science research. It is also recognized for its promising and potentially transformative applications in biotechnology, medicine and agriculture.